Translating international HIV treatment guidelines into local priorities in Indonesia - Tromp, Noor; Hontelez, Jan (Tropical medicine & international health, 2018)
Objective International guidelines recommend countries to expand antiretroviral therapy (ART) to all HIV-infected individuals and establish local-level priorities in relation to other treatment, prevention and mitigation interventions through fair processes. However, no practical guidance is provided for such priority-setting processes. Evidence-informed deliberative processes (EDPs) fill this gap and combine stakeholder deliberation to incorporate relevant social values with rational decision-making informed by evidence on these values. This study reports on the first-time implementation and evaluation of an EDP in HIV control, organised to support the AIDS Commission in West Java province, Indonesia, in the development of its strategic plan for 2014-2018. Methods Under the responsibility of the provincial AIDS Commission, an EDP was implemented to select priority interventions using six steps: (i) situational analysis; (ii) formation of a multistakeholder Consultation Panel; (iii) selection of criteria; (iv) identification and assessment of interventions’ performance; (v) deliberation; and (vi) selection of funding and implementing institutions. An independent researcher conducted in-depth interviews (n = 21) with panel members to evaluate the process. Results The Consultation Panel included 23 stakeholders. They identified 50 interventions and these were evaluated against four criteria: impact on the epidemic, stigma reduction, cost-effectiveness and universal coverage. After a deliberative discussion, the Consultation Panel prioritised a combination of several treatment, prevention and mitigation interventions. Conclusion The EDP improved both stakeholder involvement and the evidence base for the strategic planning process. EDPs fill an important gap which international guidelines and current tools for strategic planning in HIV control leave unaddressed.